A Highly Sensitive and Specific Detection Method for Mycobacterium tuberculosis Fluoroquinolone Resistance Mutations Utilizing the CRISPR-Cas13a System - Bai, Xiaopeng; Gao, Panqi; Qian, Keli; Yang, Jiandong; Deng, Haijun; Fu, Tiwei; Hu, Yuan; Han, Miaomiao; Zheng, Huizhi; Cao, Xiaoxia; Liu, Yuliang; Lu, Yaoqin; et al. (Frontiers in Microbiology, 2022)
Objectives: CRISPR-Cas13a system-based nucleic acid detection methods are reported to have rapid and sensitive DNA detection. However, the screening strategy for crRNAs that enables CRISPR-Cas13a single-base resolution DNA detection of human pathogens remains unclear. Methods: A combined rational design and target mutation-anchoring CRISPR RNA (crRNA) screening strategy was proposed. Result: A set of crRNAs was found to enable the CRISPR-Cas13 system to dramatically distinguish fluroquinolone resistance mutations in clinically isolated Mycobacterium tuberculosis strains from the highly homologous wild type, with a signal ratio ranging from 8.29 to 38.22 in different mutation sites. For the evaluation of clinical performance using genomic DNA from clinically isolated M. tuberculosis, the specificity and sensitivity were 100% and 91.4%, respectively, compared with culture-based phenotypic assays. Conclusions: These results demonstrated that the CRISPR-Cas13a system has potential for use in single nucleotide polymorphism detection after tuning crRNAs. We believe this crRNA screening strategy will be used extensively for early drug resistance monitoring and guidance for clinical treatment.